(x+y)^2-z^=a^2-(b-c)^2=(x-y)^3-x+y=16(x+y)^2-25(x-y)^2=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:18:42
(x+y)^2-z^=a^2-(b-c)^2=(x-y)^3-x+y=16(x+y)^2-25(x-y)^2=
(x+y)^2-z^=
a^2-(b-c)^2=
(x-y)^3-x+y=
16(x+y)^2-25(x-y)^2=
(x+y)^2-z^=a^2-(b-c)^2=(x-y)^3-x+y=16(x+y)^2-25(x-y)^2=
(x+y)^2-z^2
=(x+y+z)(x+y-z)
a^2-(b-c)^2
=(a-b+c)(a+b-c)
(x-y)^3-x+y
=(x-y)^3-(x-y)
=(x-y)[(x-y)^2-1]
=(x-y)(x-y+1)(x-y-1)
16(x+y)^2-25(x-y)^2
=[4(x+y)]^2-[5(x-y)]^2
=[4(x+y)+5(x-y)]*[4(x+y)-5(x-y)]
=(4x+4y+5x-5y)(4x+4y-5x+5y)
=(9x-y)(9y-x)
化简么?
=(x+y+z)(x+y-z)
=(a-b+c)(a+b-c)
=(x-y)(x-y+1)(x-y-1)
=(9x-y)(9y-x)
只要懂得平方差公式就不难做啦!a²-b²=(a+b)×(a-b)
(x+y)^2-z^2=(x+y+z)×(x+y-z)
a^2-(b-c)^2=(a+b-c)×(a-b+c)
(x-y)^3-x+y= (x-y)^3-(x-y)=(x-y)×[(x-y)²-1]=(x-y)×(x-y+1)×(x-y-1)
16(x+y)^...
全部展开
只要懂得平方差公式就不难做啦!a²-b²=(a+b)×(a-b)
(x+y)^2-z^2=(x+y+z)×(x+y-z)
a^2-(b-c)^2=(a+b-c)×(a-b+c)
(x-y)^3-x+y= (x-y)^3-(x-y)=(x-y)×[(x-y)²-1]=(x-y)×(x-y+1)×(x-y-1)
16(x+y)^2-25(x-y)^2=[4(x+y)]²-[5(x-y)]²=(9x-y)×(y-x)
收起